Mikroökonomische Determinanten und Effekte von FDI am Beispiel Baden-Württemberg - Christian Arndt; Anselm Mattes (Institut für Angewandte Wirtschaftsforschung (IAW), 2008)
In this paper we analyze the microeconomic determinants and effects of FDI using data on a representative sample of establishments in the German south-west region of Baden-Württem¬berg. With 11 million inhabitants, Baden-Württemberg exceeds the size of Sweden or Belgium. Furhter we discuss the suitability of the dataset for the analysis of international firm activity. In line with the main body of recent microeconomic theory we find that only the most produc-tive, innovative, and biggest firms invest abroad. Market seeking is the predominant motive behind FDI. At the same time a considerable number of employees is affected by the bene-fits and drawbacks of internationalization. Labor demand regressions show that FDI does not have negative implications for domestic employment. With a closer look at the motives behind FDI, we find that horizontal FDI leads to a positive labor demand shock. On the other side, vertical FDI does not have negative labor market implications.
Keywords: F21; F23; 330; Ausländische Direktinvestitionen; FDI; Arbeitsnachfrage